Influence of Knowledge Worker's Human Capital on Career Success in China - Li, Zhang (2011)
With the development of globalization and knowledge economy，knowledge has become the strategic resources of company to create value for the enterprises and it is essential element of the enterprises core competitiveness．Especially now，knowledge workers play more and more important role in the enterprises. However，since 2008，the global financial crisis out breaking, more and more workers will face choose re-employment which also including those knowledge workers with highly education and skills. Therefore, exploring the relationships between human capital and career success of knowledge workers is particularly necessary． This paper develops human capital scale through literature reviews．And with the questionnaire survey and statistics analysis of knowledge workers in Liaoning, Shandong and Shanghai provinces to make final human capital scale and at last tries to explore the relationships between human capital and career success of knowledge workers in China.